KREATIVITAS ANAK DAN CLAY TANAH LIAT - Dwi Isti Rahayu; Mulianah Khaironi (Jurnal Pendidik Indonesia (JPIn), 2018)
This study aims to develop the creativity of children aged 5-6 years in PAUD Pade Angen Tenges-Enges through the use of clay media. The type of research is qualitative study involving 12 children 5-6 years old as the subject of research. Data analysis used in this research is descriptive qualitative with data collecting technique in the form of interview, observation, and documentation. The results of the first stage of development showed that the average of creativity development of children aged 5-6 years in PAUD Pade Angen Tenges-Enges is 61.80% with the percentage of mastery learning by the teacher is 55% and increased in second stage development to 64.72% with the percentage of mastery learning by the teacher is 90% . This shows that the use of clay media can develop the creativity of children aged 5-6 years in PAUD Pade Angen Tenges-Enges.